2011
DOI: 10.1152/ajpregu.00120.2010
|View full text |Cite
|
Sign up to set email alerts
|

Bovine rumen epithelium undergoes rapid structural adaptations during grain-induced subacute ruminal acidosis

Abstract: Alterations in rumen epithelial structure and function during grain-induced subacute ruminal acidosis (SARA) are largely undescribed. In this study, four mature nonlactating dairy cattle were transitioned from a high-forage diet (HF; 0% grain) to a high-grain diet (HG; 65% grain). After feeding the HG diet for 3 wk, the cattle were transitioned back to the original HF diet, which was fed for an additional 3 wk. Continuous ruminal pH was measured on a weekly basis, and rumen papillae were biopsied during the ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

31
272
9
6

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 257 publications
(318 citation statements)
references
References 61 publications
31
272
9
6
Order By: Relevance
“…Most importantly, the success of a healed tissue depends on its functionality, i.e., the prevention of scar tissue formation and normal tissue restitution (Menke et al, 2007). In our model, microscopic images revealed that the extent of damage to the rumen following a HG challenge was limited to epithelial sloughing and to a lesser extent tight junction degradation (Steele et al 2011a); this sloughing was restored with an epithelium that was adapted to accommodate the HG challenge. Since the rumen epithelium became slightly permeable, it is possible that some microorganisms penetrated to the submucosal layers, since elevated levels of Lipopolysaccharide Binding Protein (LPSBP) were detected using the same model in subsequent experiments (Li et al, 2012;Steele et al, 2012).…”
Section: Discussionmentioning
confidence: 81%
See 3 more Smart Citations
“…Most importantly, the success of a healed tissue depends on its functionality, i.e., the prevention of scar tissue formation and normal tissue restitution (Menke et al, 2007). In our model, microscopic images revealed that the extent of damage to the rumen following a HG challenge was limited to epithelial sloughing and to a lesser extent tight junction degradation (Steele et al 2011a); this sloughing was restored with an epithelium that was adapted to accommodate the HG challenge. Since the rumen epithelium became slightly permeable, it is possible that some microorganisms penetrated to the submucosal layers, since elevated levels of Lipopolysaccharide Binding Protein (LPSBP) were detected using the same model in subsequent experiments (Li et al, 2012;Steele et al, 2012).…”
Section: Discussionmentioning
confidence: 81%
“…All amplification products were verified using BLASTN in NCBIand their dissociation curves were generated at the end of amplification to verify the presence of a single product. On the basis of previous experimental protocols (Steele et al, 2011a), GAPDH was determined to be the most stable housekeeping gene in the rumen papillae and was thus used in this study. For each week, the relative mRNA expression of genes was calculated using the inverse of qPCR efficiency raised to Delta Ct (∆Ct) using the Pfaffl method (Pfaffl et al, 2004).…”
Section: Animals and Managementmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, in response to acidosis, the rate of metabolism and proliferation of stratified squamous epithelium increase dramatically, resulting in premature transition of cells into the keratinous layer, a condition known as parakeratosis (Kleen et al, 2003;Steele et al, 2011;Plaizier et al, 2012). All animals that received any type of concentrate had a darker colour than those fed on alfalfa.…”
Section: Digestive Tract Characteristicsmentioning
confidence: 99%